2019
DOI: 10.20944/preprints201910.0232.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Satellite Retrieval of Downwelling Shortwave Surface Flux and Diffuse Fraction under All Sky Conditions in the Framework of the LSA SAF Program (Part 1: Methodology)

Abstract: Several studies have shown that changes in incoming solar radiation and variations of the diffuse fraction can significantly modify the vegetation carbon uptake. Hence, monitoring the incoming solar radiation at large scale and with high temporal frequency is crucial for this reason along with many others. The EUMETSAT Satellite Application Facility for Land Surface Analysis (LSA SAF) operationally disseminates in near real time estimates of the downwelling shortwave radiation at the surface since 2005. This p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The direct and diffuse solar irradiance are essential for estimating solar irradiance under arbitrary surface orientations [3][4], obstructed environments [5], within interior spaces [6], for building energy simulations, impact on photovoltaic systems and the photosynthesis potentials in agricultural/forestry analysis and planning [7] [8]. Recent studies have shown and measured the positive effect that Diffuse irradiation has on increasing canopy light use efficiency (LUE) in the Amazon Rain Forrest and related vegetative carbon uptake [9][10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…The direct and diffuse solar irradiance are essential for estimating solar irradiance under arbitrary surface orientations [3][4], obstructed environments [5], within interior spaces [6], for building energy simulations, impact on photovoltaic systems and the photosynthesis potentials in agricultural/forestry analysis and planning [7] [8]. Recent studies have shown and measured the positive effect that Diffuse irradiation has on increasing canopy light use efficiency (LUE) in the Amazon Rain Forrest and related vegetative carbon uptake [9][10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…The direct and diffuse solar irradiance are essential for estimating solar irradiance under arbitrary surface orientations [3] [4], obstructed environments [5], within interior spaces [6], for building energy simulations, impact on photovoltaic systems and the photosynthesis potentials in agricultural/forestry analysis and planning [7] [8]. Recent studies have shown and measured the positive effect that Diffuse irradiation has on increasing canopy light use efficiency (LUE) in the Amazon Rain Forrest and related vegetative carbon uptake [9][10] [11].…”
Section: Introductionmentioning
confidence: 99%